Model-based spectral analysis of photon propagation through nanoparticle-labeled epithelial tissues - Cihan, Can; Arifler, Dizem (Spie-Int Soc Optical Engineering, 2011)
Metal nanoparticles can function as optical contrast enhancers for reflectance-based diagnosis of epithelial precancer. We carry out Monte Carlo simulations to model photon propagation through normal tissues, unlabeled precancerous tissues, and precancerous tissues labeled with gold nanospheres and we compute the spectral reflectance response of these different tissue states. The results indicate that nanoparticle-induced changes in the spectral reflectance profile of tissues depend not only on the properties of these particles but also on the source-detector geometry used. When the source and detector fibers are oriented side by side and perpendicular to the tissue surface, the reflectance intensity of precancerous tissue is lower compared to that of normal tissue over the entire wavelength range simulated and addition of nanospheres enhances this negative contrast. When the fibers are tilted toward each other, the reflectance intensity of precancerous tissue is higher compared to that of normal tissue and labeling with nanospheres causes a significant enhancement of this positive contrast. The results also suggest that model-based spectral analysis of photon propagation through nanoparticle-labeled tissues provides a useful framework to quantify the extent of achievable contrast enhancement due to external labeling and to assess the diagnostic potential of nanoparticle-enhanced optical measurements.
Conference on Clinical and Biomedical Spectroscopy and Imaging II -- MAY 24-26, 2011 -- Munich, GERMANY
Keywords: Epithelial precancer; Monte Carlo modeling; nanoparticles; optical spectroscopy; photon propagation; reflectance